Influencing factors for placenta accreta in recent 5 years: a systematic review and meta-analysis. (3rd June 2022) - Hou, Yi-Ping; Lommel, Lisa; Wiley, James; Zhou, Xi-Hong; Yao, Min; Liu, Sai; Peng, Jin-Li
Abstract: Objective: Assess influencing factors for placenta accreta in pregnant women documented in recent literature. Methods: A systematic review and meta-analysis were conducted based on English- and Chinese-language articles published from January 2014 to June 2019. Articles were retrieved from the following Chinese databases, CNKI, Wanfang Data, China Science and Technology Journal Database, CBM and English databases, PubMed, Web of Science, the Cochrane Library and Embase. Results: Eleven studies with 2, 152, 014 cases were included in the meta-analysis. The odds ratios of influencing factors were as follows: hypertension 2.51 (95% CI, 1.50–4.20), multifetal gestations 1.90 (95% CI, 1.26–2.88), male fetus 0.79 (95% CI, 0.74–0.84), and low socioeconomic status 0.51 (95% CI, 0.37–0.71). Conclusion: Evidence from English- and Chinese-language literature indicates that hypertension and multifetal gestations are risk factors for placenta accreta, while male fetus and low socioeconomic status are protective factors.